Catalytic asymmetric coupling of vinylogous species via deconjugated butenolide addition to vinylogous imines in situ generated from arylsulfonyl indoles - Yuan, Shu-Pei; Zhang, Xia-Yan; Jia, Yun-Qing; Wang, Zhen-Hua; Zhao, Jian-Qiang; You, Yong; Zhou, Ming-Qiang; Yuan, Wei-Cheng (Chemical communications (Cambridge, England), 2021)
An efficient catalytic asymmetric coupling of vinylogous species is developed via deconjugated butenolide addition to vinylogous imines in situ generated from arylsulfonyl indoles. With quinine-derived bifunctional squaramide as the catalyst, a series of structurally diverse enantioenriched sec -alkyl-3-substituted indoles containing valuable γ,γ -disubstituted butenolide moieties and adjacent quaternary-tertiary stereocenters are obtained in synthetically viable results (up to 97% yield, 77 : 23 dr and 97% ee).